Management of shopping centres located in socio-economically deprived areas - Mphahlele, Charmaine (Department of Construction Economics and Management, 2025)
This research firstly discusses the evolution of retail and retail centres in South Africa's socio economically deprived areas, and this is followed by a discussion on the effective management and maintenance of the retail centres in these areas. This study examines both the challenges and the opportunities that come with managing shopping centres in socio-economically deprived areas in South Africa. The areas referred to as socio-economically deprived areas in this research are those that were racially demarcated for the dwelling of non-white people in Apartheid South Africa. These socio-economically deprived areas form a fundamental populus in the South African economy, and although this is the case these areas were serviced by ‘spaza shops' and neighbourhood informal retailers. This indicated a market gap as there was a population group able to spend money on retail purchases, but it was an under-served population group due to the lack of retail centres close to it. Once South Africa gained its democracy, there was economic relief brought to the population of socio-economically deprived areas and some of the country's largest retail and property development organisations took the opportunity to close this gap. Retail centres began to emerge in socio-economically deprived areas as they became an ingrained part of South African culture and economy. A qualitative research methodology was adopted using semi-structured interviews to gather data from industry experts. Data saturation was achieved at the 8th interview. The interview transcripts were analysed using thematic analysis to identify emergent themes that address the research question. The findings of the study reveal that shopping centres in socio economically deprived areas face a range of challenges, including high crime rates, poor infrastructure, and limited access to resources. However, the study also identifies opportunities for improving the management of shopping centres in these areas, such as community engagement, strategic partnerships, and innovative marketing strategies. This research established that the current adopted Asset Management and Property Management theoretical frameworks fail to reflect what “practically” needs to occur to be able to improve the management of retail centres in socio-economically deprived areas. This will allow for the effective management of those retail centres whilst considering the unique dynamics of the socio-economically deprived areas known as townships and rural areas. iii Based on the findings, the study recommends an alternative model for the management of shopping centres in socio-economically deprived areas in South Africa. The model emphasises the importance of community engagement, stakeholder collaboration, and sustainable development practices. The study concludes that effective management of shopping centres in socio-economically deprived areas requires a holistic approach that considers the unique challenges and opportunities of these areas. Overall, this research contributes to the existing literature on the management of shopping centres in socio-economically deprived areas in South Africa. The study provides valuable insights into the challenges and opportunities of managing shopping centres in these areas and offers recommendations for improving the management of shopping centres in socio economically deprived areas.